Lexical Variations of Angkola In The City of Padang Sidimpuan - Fitri Angreni Lubis; Dwi Widayati; Gustianingsih (CV. Inara, 2021)
This study aims to describe the distribution of lexical variations of the Angkola language in Paandgsidimpuan City. To find out the distribution, the researcher used the field pupuan method as a data collection technique. The research data uses a list of dialectological questions that have been validated by the Language Development and Development Agency, which contains 200 basic Swadesh vocabularies. The results of the analysis show that the lexical variations of the Angkola language in Paandgsidimpuan City show the highest distribution of variations, namely a group of two etymons with 53 glosses, a group of three etymons with 33 glosses, a group of four etymons with 6 glosses and a group of five etymons with 1 identified gloss.